Henry and Mudge and the careful cousin : the thirteenth book of their adventures - Rylant, Cynthia (Rylant, Cynthia. Henry and Mudge books., 1994)
At first Henry's very neat cousin doesn't like the cookies from under his bed or Mudge's slobbery kisses, but when they all play frisbee, she begins to enjoy her visit.